HISTORICAL DEVELOPMENT AND DIALECTAL VARIATIONS OF THE PLURAL CATEGORY IN TURKIC LANGUAGES - Roya Nadir kizi Gahramanova (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
The quantitative differentiation of nouns in Turkic languages is considered one of the most stable and ancient grammatical categories of the language. The concept of plurality is not only a semantic category that emerged from communicative needs, but also a structural element that has played an important role in the formation of the morphological system.